Perbandingan Sistem Pendukung Keputusan Metode SAW Dengan TOPSIS dalam Pemilihan Guru Terbaik (Studi Kasus: SMPN 2 Rangkasbitung) - Mulyanti, Ika (Universitas Pamulang, 2023)
SMPN 2 Rangkasbitung is one of the junior high schools in Rangkasbitung which routinely holds the selection of the best teachers every year. However, so far the selection of the best teachers has still faced obstacles, where the best teacher assessment system still uses the questionnaire method. The results of the questionnaire are then submitted to the assessment team to assess which teachers will be selected as the best teachers. It often happens that the results of these assessments are very subjective and inaccurate. Finally, the results obtained were always in doubt and caused debate among the assessment team. To solve this problem, so that the results of the assessment are more objective, a Decision Support System (SPK) using the Simple Additive Weighting (SAW) method and the Technique for Order Preference By Similarity to Ideal Solution (TOPSIS) is used. In this study, researchers used 2 methods at once to find out the comparison. Which method is the best in overcoming the problem of determining the Best Teacher at SMPN 2 Rangkasbitung. In implementing this method, the application uses the PHP programming language, and data storage uses MySQL. The results of the comparison of the two methods will determine which method is the best for determining the best teacher. In addition, researchers also use web-based applications to simplify the process of selecting the best teacher by applying the Simple Additive Weighting (SAW) and Technique for Order Preference By Similarity to Ideal Solution (TOPSIS) methods as a comparison at SMPN 2 Rangkasbitung.